tumblr.com/tagged/vaporwave: redes de sentidos articuladas pela hashtag vaporwave - Maiana Abi-samara dos Santos Castro (2017)
Vaporwave is a term associated with a style of music and imagery strongly marked by traces of digital intervention and a nostalgic retake on representations of a technological future from the late twentieth century. The production associated to vaporwave is characterized by practices of media appropriation, recombination and repetition, with the Internet as its main means of propagation. We point out that vaporwave is not understood as something fixed and it has the potential to be shaped by its use associated with mediatic contents and co-occuring terms, which support and effect the construction of its shared meanings. Thus, the object of this research is the manifestation of the term vaporwave as a hashtag on Tumblr. In order to map the networks of meanings that emerge articulated by the presence of this hashtag, we propose a hybrid methodological approach with two main procedures. First, there is the automated collection of a corpus consisting of 44,000 posts containing #vaporwave on Tumblr and their respective metadata. Some aspects of this structured data are assessed, as well as the top 100 hashtags that co-occur with #vaporwave. In a second moment, using a cartographic approach taken from the considerations on rhizome by Deleuze and Guattari (2000) and from the considerations by Passos, Kastrup and Escóssia (2015) we register the reading of five current posts and another five from the initial period of use of the hashtag on Tumblr. Finally, we note that vaporwave articulates (and is articulated by) a network of meanings that indicates both critical and affirmative, often ironic, reflections on a mode of existence intensely immersed in computational technologies.